Risk Factor Evaluation of Non Alcoholic Fatty Liver Disease in Lean Individual (Journal of Chittagong Medical College Teachers' Association, 2022)
Background : Non-Alcoholic Fatty Liver Disease (NAFLD) is epidemic around the world. Bangladesh is also experiencing an increasing trend of NAFLD. Obesity is a common clinical phenotype associated with NAFLD, which is linked to metabolic syndrome and related comorbidities, including type II diabetes, hypertension and dyslipidemia. Clearly, not all obese subjects develop NAFLD and NAFLD also can be found in non-obese patients. This subset of individuals, known to have ‘lean NAFLD’ or ‘non-obese NAFLD’, is growing increasingly prevalent. NAFLD in lean patients appears to be more common among Asians. So it is important to look for risk factors for NAFLD in lean patients for prevention of advanced liver disease. The objective of our study was to find out the risk factors of NAFLD in lean (Nonobese) individual.Materials and methods: It was prospective observational study done on 100 patients attending in the Gastroenterology Department and OPD of Chittagong Medical College Hospital after approval of Ethical and Review Committee of CMC and grant from DGHS. Total 100 patients having 18 to 65 years of age, were taken as study subjects who met inclusion criteria. Informed written consent was obtained from the patients or attendant after full explanation of the purpose of the study. Fasting Blood Glucose (FBS) Fasting lipid profile, SGPT, SGOT, Ultrasonography of hepatobiliary system and Fibrosan were done. All necessary data was included in the data collection sheet and was analyzed by Microsoft excel and SPSS-23.Results: 100 patients were included in this study. Mean age of this study with age was in between 18 years to 65 years.Male to female ratio was 3:1 in the studied population.The majority of the lean patient with NAFLD (31%) was in the age group 40-49 years. The majority of the lean patient with NAFLD (83%) was in normal BMI range 18.5-22.99 kg/m2 and 13% had BMI